POPULAR OR POPULER? COMPARING AI AND HUMAN TRANSLATION OF NONCE WORDS IN WICKED’S INDONESIAN SUBTITLES - Abdillah, Taufik Eryadi; Fanny Puji Rakhmi; Ina Sukaesih; Farizka Humolungo; Septina Indrayani (Universitas Islam Negeri Sunan Gunung Djati, 2025)
This study investigates the process of translating nonce words in Indonesian subtitles of the musical fantasy film Wicked, focusing on the challenges posed by highly creative and humorous expressions that remain underexplored in audiovisual translation studies. Set in the magical land of Oz, the film incorporates playful and imaginative expressions like Galindafied and braverism, which present unique translation difficulties. The study employs content analysis to compare human-generated subtitles from Apple TV with AI-generated subtitles produced by ChatGPT. While both human and AI translations tend to convey the general meaning of the nonce words, they fail to capture the stylistic and humorous nuances present in the source language. Human translations can be literal or omit creative expressions entirely, suggesting that neither method fully encapsulates the inventiveness and playfulness of the source language. This study underscores the importance of developing more adaptable strategies for translating highly creative audiovisual texts.